Fluxograma para o manejo de pessoas idosas com alterações de deglutição pós acidente vascular cerebral - Chaves, Simone Pereira Lins (2019)
Introduction: The repercussions of aging on society are considerable and generate a need for a more dynamic look at elders and their natural consequences, as well as on the most frequent morbidities. One of these is the cerebrovascular accident (CVA), which is among the risk actors of old age and whose sequels are a health problem, evidencing the need for care to the elderly person. Objectives: To identify in the scientific productions post-CVA swallowing disorders in the elderly person; to know the prevalence of post-CVA swallowing disorders in the elders assisted in a home care service; and to build a flowchart for the management of elderly people with post-CVA swallowing disorders. Methodology: This was a methodological research with a quantitative approach, carried out in December 2018, structured in the following phases: an integrative review of the literature on post-CVAswallowing disorders in elders; a documentary study in medical records, observing sociodemographic, clinical variables and prevalence of post-CVA swallowing disorders in patients attended in the home care service in 2017 and later the construction of the flowchart for the management of elderly people with post-CVA swallowing disorders. Data were categorized and placed in a spreadsheet in Microsoft Excel. Subsequently, they were submitted to descriptive statistical analysis (absolute frequency and percentage), using the software R statistical program. Results: 139 medical records of elderly people assisted by the home care service of the city of João Pessoa in 2017 were analyzed. After applying the inclusion and exclusion criteria, the sample consisted of 38 charts, which contained data related to the characteristics of the elderly person, subsidizing the construction of the flowchart as a technological tool for the care to the elderly person. Overarching findings regarding the prevalence of males in the involvement of CVA, elderly people aged between 71-80 years, and the pulmonary aspects are stable, regular nutritional and food with swallowing orally and in all food consistencies and swallowing with difficulty when swallowing. Conclusion: Based on the data obtained from the research, elders present several post-CVA swallowing disorders, which compromise the health and quality of life of the affected individuals. The flowchart presented in this study can help health professionals who attend to this demand, conducting, as early as possible, to the speech therapist, as well as the multidisciplinary team.